Transient radiative hydromagnetic free convection flow past an impulsively started vertical plate with uniform heat and mass flux - Prasad Ramachandra V.; Reddy Bhaskar N.; Muthucumaraswamy R. (Theoretical and Applied Mechanics, 2006)
The interaction of free convection with thermal radiation of viscous incompressible MHD unsteady flow past an impulsively started vertical plate with uniform heat and mass flux is analyzed. This type of problem finds application in many technological and engineering fields such as rocket propulsion systems, space craft re-entry aerothermodynamics, cosmical flight aerodynamics, plasma physics, glass production and furnace engineering .The Rosseland approximation is used to describe the radiative heat transfer in the limit of the optically thin fluid. The non-linear, coupled equations are solved using an implicit finite difference scheme of Crank-Nicolson type. Velocity, temperature and concentration of the flow have been presented for various parameters such as thermal Grashof number, mass Grashof number, Prandtl number, Schmidt number, radiation parameter and magnetic parameter. The local and average skin friction, Nusslet number and Sherwood number are also presented graphically. It is observed that, when the radiation parameter increases the velocity and temperature decrease in the boundary layer. .